Optimization of mango peel pectin-based edible film - Marquez, Kristelle Dianne Nicole A.
The water vapour permeability of edible film derived from Carabao mango peel pectin and prepared via casting method was determined. Using Design Expert 7.0.0, Central Composite Design was utilized to determine the optimal concentration of mango peel pectin and glycerol in developing edible films with minimal permeance. The effect of pectin (1.5, 2.5, 3.5%) and glycerol (30, 50, 70%) on the response variable were observed. The results suggested quadratic model for both independent variables but was found to be insignificant in the analysis (p=0.3959) as supported by the significance of lack-of-fit (p<0.0001).This implies that the range of pectin and glycerol concentration used do not significantly affect water vapour permeability of developed edible film. Thus, setting the amount of pectin and glycerol at the minimum will not have considerable effect on the water vapour permeability of produced film.